(untitled) (International Journal of Mathematics and Physics, 2025)
This study focuses on numerical modeling of thoracic aortic hemodynamics in patients with coarctation, a congenital narrowing of the vessel lumen that impairs blood flow and increases hemodynamic load. The aim of the study was to identify the influence of geometric changes in the aorta on the distribution of velocity, pressure, and shear stress using computational fluid dynamics (CFD) methods. The mathematical model is based on the Navier-Stokes equations for an incompressible non-Newtonian fluid, which describes the rheological properties of blood. Calculations were performed using the finite volume method with an explicit time-dependent scheme for two geometric configurations—normal and pathological. Analysis of the resulting velocity and pressure fields revealed that with coarctation, the maximum velocity increases by approximately 1.6 times, and the pressure difference between the ascending and descending aorta reaches 0.6 kPa. The shear stress distribution revealed localized areas of extreme values that potentially contribute to endothelial dysfunction. This study contributes to the development of personalized blood flow modeling and demonstrates the potential of CFD methods for assessing hemodynamic disturbances in vascular pathologies, which has practical implications for preliminary diagnosis and treatment planning. Keywords: hemodynamics, coarctation of the aorta, computational fluid dynamics, CFD, numerical modeling.